2015
DOI: 10.4174/astr.2015.89.4.190
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus conventional laparoscopic surgery for rectal cancer: systematic review and meta-analysis

Abstract: PurposeRobotic surgery (RS) overcomes the limitations of previous conventional laparoscopic surgery (CLS). Although meta-analyses have been published recently, our study evaluated the latest comparative surgical, urologic, and sexual results for rectal cancer and compares RS with CLS in patients with rectal cancer only.MethodsWe searched three foreign databases (Ovid-MEDLINE, Ovid-Embase, and Cochrane Library) and five Korean databases (KoreaMed, KMbase, KISS, RISS, and KisTi) during July 2013. The Cochrane Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 50 publications
(91 reference statements)
7
50
1
Order By: Relevance
“…There are only a few studies whose data were homogeneous enough to permit a meta-analysis. However, this has already been performed by two previous systematic reviews[46,47] which combined the data of three studies. We discuss these systematic reviews in our discussion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only a few studies whose data were homogeneous enough to permit a meta-analysis. However, this has already been performed by two previous systematic reviews[46,47] which combined the data of three studies. We discuss these systematic reviews in our discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it should be mentioned that two review articles have performed meta-analyses on male urological and sexual function scores of patients receiving robotic vs laparoscopic rectal surgery[46,47]. For male urological function, the reviews pooled the data from three studies and found that at 3 mo there was a significant difference of IPSS scores in favour of the robotic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case-controlled analysis comparing TME between robotic and laparoscopic methods did not show any significant difference in the amount of blood loss (30). A separate meta-analysis review reaffirmed these findings (31).…”
Section: Estimated Blood Lossmentioning
confidence: 88%
“…To date, this surgery has been conducted in 5 cases at our department. Because robotic surgery enables microsurgery, its efficacy is expected as a means of surgical treatment of rectal cancer which requires preservation of urinary and sexual function 31) . At present, an RCT designed to compare perioperative complications and the long-term prognosis for rectal cancer associated with robotic surgery and laparoscopic surgery is under way at 20 facilities across the world 32) .…”
Section: Robotic Surgerymentioning
confidence: 99%